2003
DOI: 10.4049/jimmunol.171.11.6154
|View full text |Cite
|
Sign up to set email alerts
|

Apoptosis-Associated Speck-Like Protein Containing a Caspase Recruitment Domain Is a Regulator of Procaspase-1 Activation

Abstract: Apoptosis-associated speck-like protein containing a caspase recruitment domain (ASC)/target of methylation-induced silencing/PYCARD represents one of only two proteins encoded in the human genome that contains a caspase recruitment domain (CARD) together with a pyrin, AIM, ASC, and death domain-like (PAAD)/PYRIN/DAPIN domain. CARDs regulate caspase family proteases. We show here that ASC binds by its CARD to procaspase-1 and to adapter proteins involved in caspase-1 activation, thereby regulating cytokine pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
182
1
4

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 214 publications
(196 citation statements)
references
References 43 publications
(47 reference statements)
9
182
1
4
Order By: Relevance
“…Previous studies indicate that TMS1 is upregulated in response to cytokines such as IL-1b, IFN-g, TNFa and LPS in immune cells (Shiohara et al, 2002;Stehlik et al, 2003), however, the mechanism of this regulation was not determined. We found here that TMS1 is also regulated by TNFa in breast epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Previous studies indicate that TMS1 is upregulated in response to cytokines such as IL-1b, IFN-g, TNFa and LPS in immune cells (Shiohara et al, 2002;Stehlik et al, 2003), however, the mechanism of this regulation was not determined. We found here that TMS1 is also regulated by TNFa in breast epithelial cells.…”
Section: Discussionmentioning
confidence: 92%
“…Previous studies have shown that TMS1 is induced in these cell types in response to proinflammatory stimuli including IL-1b, LPS and TNFa (Shiohara et al, 2002;Stehlik et al, 2003), although the exact mechanism of this upregulation has not been addressed. TMS1 is also expressed in many epithelial cell types (Masumoto et al, 2001).…”
Section: Resultsmentioning
confidence: 99%
“…It is well established that ASC is an important mediator of caspase-1 activation, and an homophilic CARD-CARD interaction between ASC and procaspase-1 has been reported. 118 Accordingly, macrophages from ASC-deficient mice are defective in caspase-1 activation (and IL-1b secretion) in response to TLR stimulation or activation by the Gram-negative bacterial pathogen, S. typhimurium. 67 The role of ASC in the activation of the NF-kB pathway remains somewhat controversial.…”
Section: Ascmentioning
confidence: 99%
“…The inflammasome component Asc has been described as an activator of procaspase-1 21 or as a modulator, leading to activation of procaspase-1 at low and inhibition at higher concentrations. 30 As the EBBP homolog Pyrin binds to Asc, 20 we tested if this is also the case for EBBP. Therefore, we performed co-IPs of HA-tagged EBBP and Asc fusion proteins tagged with an epitope of the vesicular stomatitis virus (VSV) or with a Flag tag.…”
Section: Ebbp Does Not Interact With Asc But With Procaspase-1 and Nalp1mentioning
confidence: 99%